Empowering students with technology - November, Alan C. 4 0 16; 5 National Association of Secondary School Principals (U.S.) (Thousand Oaks, CA : Corwin, 2010)
Offers tips and sample activities for teachers to encourage student understanding of technological devices, including the use of computers for Internet research, and provides a list of fifty Web sites.
A Joint Publication With National Association of Secondary School Principals.
Includes bibliographical references (p. 107-108) and index.
Professional;Professional.
Keywords: 2 -- 0; 6; Experimental methods. -- Computer-assisted instruction;Internet in education;Educational innovations;Computer-assisted instruction;Education -- United States.;United States.;United States.;United States.;United States; 20; 2